2009
DOI: 10.1002/esp.1703
|View full text |Cite
|
Sign up to set email alerts
|

Prescribed‐fire effects on rill and interrill runoff and erosion in a mountainous sagebrush landscape

Abstract: Changing fire regimes and prescribed-fire use in invasive species management on rangelands require improved understanding of fire effects on runoff and erosion from steeply sloping sagebrush-steppe. Small (0·5 m 2 ) and large (32·5 m 2 ) plot rainfall simulations (85 mm h -1 , 1 h) and concentrated flow methodologies were employed immediately following burning and 1 and 2 years post-fire to investigate infiltration, runoff and erosion from interrill (rainsplash, sheetwash) and rill (concentrated flow) processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
263
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(272 citation statements)
references
References 28 publications
8
263
1
Order By: Relevance
“…For example, studies in rangeland regions of the US found moderate increases in flow, infiltration, and erosion rates after major wildfires, with trends continuing for as long as 15 years (Emmerich and Cox, 1994;Pierson et al, 2009;Hester et al, 1997;Kinoshita and Hogue, 2015). Fires in chaparral environments, such as in southern California, exhibited increased flows of up to as much as 2 orders of magnitude, with much of this occurring in the dry season (Coombs and Melack, 2013;Hogue, 2011, 2015;Loáiciga et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies in rangeland regions of the US found moderate increases in flow, infiltration, and erosion rates after major wildfires, with trends continuing for as long as 15 years (Emmerich and Cox, 1994;Pierson et al, 2009;Hester et al, 1997;Kinoshita and Hogue, 2015). Fires in chaparral environments, such as in southern California, exhibited increased flows of up to as much as 2 orders of magnitude, with much of this occurring in the dry season (Coombs and Melack, 2013;Hogue, 2011, 2015;Loáiciga et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The amount of material mobilized in a particular watershed is dependent on the intensity and duration of rainfall, groundcover, vegetation, slope gradient, and recent fire history (Renard et al, 1997;Pierson et al, 2009). Between 70 and 90% of the soil and associated carbon mobilized from eroding landscapes is deposited within the source or adjacent watersheds (Gregorich et al, 1998;Stallard, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The loss of vegetation after high severity fires is one of the main drivers of post-fire erosion, as vegetation plays a major role in stabilizing eroding soils (Shakesby et al, 1993;Larsen et al, 2009;Pierson et al, 2009). In extreme cases, this loss of vegetation can lead to debris and ash flows when intense rainfall events occur on recently burned hillslopes .…”
Section: Introductionmentioning
confidence: 99%
“…First, disturbance by heavy equipment during rehabilitation can negatively impact any desired species that survived the wildfire. Second, and most importantly, disturbing a post-fire landscape can result in accelerated soil erosion (Pierson et al 2009, Miller et al 2012. Wildfires typically negatively impact surface soil quality through loss of organic matter and exacerbation of hydrophobicity effects (Pierson et al 2014, Williams et al 2014a, resulting in reduced infiltration capacity, increased run-off, and generally poor seed germination (Pierson et al 2002, Ravi et al 2006, 2007, Pierson et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Wildfires typically negatively impact surface soil quality through loss of organic matter and exacerbation of hydrophobicity effects (Pierson et al 2014, Williams et al 2014a, resulting in reduced infiltration capacity, increased run-off, and generally poor seed germination (Pierson et al 2002, Ravi et al 2006, 2007, Pierson et al 2011. However, the loss of vegetation cover from wildfire leaves these soils exposed to erosion by wind and water (Pierson et al 2009), and disturbing these soil surfaces further during post-fire rehabilitation can greatly increase soil erodibility (Williams et al 2014b). …”
Section: Introductionmentioning
confidence: 99%